Incidence of congenital syphilis in a city in western Paraná (Research, Society and Development, 2023)
Syphilis is an infectious disease that consists in a systemic infection, occurs by the dissemination of Treponema pallidum and presents high rates of vertical transmission, which may reach 100%. The diagnosis of gestational syphilis is simple and its screening is mandatory during prenatal care. Still, this disease has a high prevalence worldwide. Several factors have been implicated in the increase in the number of syphilis cases, the main one being ineffective prenatal care. Objectives: To study the prevalence of congenital syphilis (CS) in a western municipality of Paraná, highlighting its role as a quality indicator of prenatal care and to assess the impact of the COVID-19 pandemic in this period. Method: quantitative study of cases of CS that occurred in the municipality of Cascavel-PR, in the period from August 1, 2018 to August 1, 2021. Results: 55 cases of congenital syphilis were reported, with the majority in the year 2021 with 34.5% of the total cases. Excluding those filled out as ignored or with missing data, of the 7 pregnant women who underwent treatment with Penicillin, 100% had live newborns, this being a statistically relevant finding (p